Characterization of the Temporal Pattern of Blood Protein Digestion in Rhodnius prolixus: First Description of Early and Late Gut Cathepsins - Henriques, Bianca Santos; Gomes, Bruno; Oliveira, Pedro Lagerblad; Garcia, Elói de Souza; Azambuja, Patrícia; Genta, Fernando Ariel (Frontiers in Physiology, 2021)
Rhodnius prolixus is one important vector for the parasite Trypanosoma cruzi in Latin America, where Chagas disease is a significant health issue. Although R. prolixus is a model for investigations of vector–parasite interaction and transmission, not much has been done recently to further comprehend its protein digestion. In this work, gut proteolysis was characterized using new fluorogenic substrates, including optimum pH, inhibition profiles, and tissue and temporal expression patterns. Each protease possessed a particular tissue prevalence and activity cycle after feeding. Cathepsin L had a higher activity in the posterior midgut lumen, being characterized by a plateau of high activities during several days in the intermediate phase of digestion. Cathepsin D showed high activity levels in the tissue homogenates and in the luminal content of the posterior midgut, with a single peak 5 days after blood feeding. Aminopeptidases are highly associated with the midgut wall, where the highest activity is located. Assays with proteinaceous substrates as casein, hemoglobin, and serum albumin revealed different activity profiles, with some evidence of biphasic temporal proteolytic patterns. Cathepsin D genes are preferentially expressed in the anterior midgut, while cathepsin L genes are mainly located in the posterior portion of the midgut, with specific sets of genes being differently expressed in the initial, intermediate, or late phases of blood digestion. Significance Statement This is the first description in a non-dipteran hematophagous species of a sequential protease secretion system based on midgut cathepsins instead of the most common insect digestive serine proteases (trypsins and chymotrypsins). The midgut of R. prolixus (Hemiptera) shows a different temporal expression of proteases in the initial, intermediate, and late stages of blood digestion. In this respect, a different timing in protease secretion may be an example of adaptative convergence in blood-sucking vectors from different orders. Expanding the knowledge about gut physiology in triatomine vectors may contribute to the development of new control strategies, aiming the blocking of parasite transmission.